Impact of clomazone on bacterial communities in two soils - He, Hairong; Huang, Jiarui; Zhao, Zhenzhu; Feng, Weisheng; Zheng, Xiaoke; Du, Pengqiang (Frontiers in Microbiology, 2023)
Two agricultural soils were used to research the impact of clomazone on bacterial network complexity, composition, and stability. The soils were treated with three concentrations of clomazone (0, 0.8, 8, and 80 mg kg -1 ) and carried out in an incubator. Bacterial network nodes, links, and average degrees were all decreased by 9-384, 648-829, and 0.703-2.429, respectively. Based on keystone nodes, nodes topological roles were also influenced by clomazone. Bacterial network composition was also impacted based on ANOSIM and network dissimilarity. Compared with control and clomazone treatments in both soils, the ANOSIM between control and all clomazone treatments were all higher than 0.6, network dissimilarities were 0.97-0.98, shared nodes were 131-260, and shared links were 12-100. The bacterial network stability was decreased by clomazone with decreased robustness by 0.01-0.016 and increased vulnerability by 0.00023-0.00147 in two soils. There were less bacterial network modules preserved after clomazone treating, and the bacterial network community functions were also impacted in both soils. Based on these results, soil bacterial species connections, modularization, and network stability were significantly impacted by clomazone.